PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM JUAL BELI ONLINE YANG MENGGUNAKAN SITUS WEB IKLAN DI FACEBOOK DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Diky Dikrurahman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Legal protection related to buying and selling online using the web on Facebook is a problem that occurs in Kuningan Regency, which started with the absence of laws or regulations regarding online buying and selling, causing fraud to occur for goods and or services that do not match what is advertised. This research will reveal legal protection for consumers in online buying and selling transactions through the Facebook advertising web and reveal the responsibilities of business actors in dealing with violated consumer rights. The purpose of this research is to find out how legal protection is for consumers and to find out how business actors are responsible for consumer rights. In this study, the authors used empirical juridical methods, research specifications using descriptive analysis. The form of protection given to consumers in buying and selling online is equated with the protection given to conventional buying and selling. The occurrence of a legal relationship between a business actor and a consumer is when the perpetrator makes a promise and all information relating to the goods and/or services offered to consumers on when providing advertisements, brochures, or promotions. The responsibility of business actors to consumers is by compensating for losses, refunding money or being able to send goods and or services that are in accordance with what consumers want. Legal protection for consumers who use online buying and selling through Facebook advertising is intended so that consumers get legal certainty.